Práticas pedagógicas contemporâneas: uma análise da série Destino Educação: Escolas Inovadoras - Neves, Antônia Regina Gomes (Universidade do Vale do Rio dos Sinos, 2020)
The research presented here aims to investigate, understand and describe the pedagogical practices developed in the innovative schools of the Destino: Educação - Innovative Schools series. To this end, a documentary film analysis was developed, comprising 26 episodes of the documentary series. The reading key was developed from the pedagogical practice as an experience matrix. Four pedagogical practices that stand out in the series were mapped, they are: study guides, research projects, conducting by question and tutoring. Analytically, it is pointed out that the pedagogical practices that make up innovative teaching are put into action in the schools of the Destino: Educação - Innovative Schools series, by the performance of teachers who share and multiply pedagogical knowledge with their students, teaching them to lead themselves and learn to learn, through an emphasis on discipline, hierarchical vigilance, examination and (self) control of teaching and learning processes. Thus, upon completing the Modernity project in innovative schools, discipline and control appear mobilized by the student's interest, desire and responsibility, so that each student becomes responsible for their learning and that of their colleagues, even though teacher is also responsible for the same process. The school curriculum is developed by schools in the model of a “labyrinth curriculum”, in which students can choose when they move through each corridor, but must go through the entire labyrinth, in which the teacher has the task of leading the student from inside the labyrinth and, at the same time, to have a wide view of the outside of the labyrinth, in order to ensure that everyone has passed through all the corridors. The teaching performance fades in the task of modern teaching as it intensifies in the planning and constant and systematic monitoring of all students and each one. It defends the thesis that innovation is the power of the contemporary, expressed by the exacerbation of hypermodern components mobilized by students, teachers and school managers.
Keywords: Inovação; Práticas pedagógicas; Matriz de experiência; Destino: Educação – Escolas Inovadoras; Innovation; Pedagogical practices; Experience matrix; ACCNPQ::Ciências Humanas::Educação